Metabolic Profile of People Living with HIV in a Treatment Hub in Manila, Philippines: A Pre- and Post-Antiretroviral Analysis - Francisco, Christian; Gonzales, Eddieson; Yu, Marc Gregory; Salvaña, Edsel Maurice; Abad, Cybele; Reganit, Paul Ferdinand; Maningat, Patricia; Sison, Olivia; Alejandria, Marissa (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives. People living with HIV (PLHIV) are susceptible to develop dyslipidemia and hyperglycemia. This study aims to determine the prevalence of these metabolic derangements among Filipino PLHIV. Methodology. We reviewed 635 medical records in a treatment hub in Manila, Philippines from January 2004 to July 2016. Logistic regression analysis was done to determine factors associated with dyslipidemia and hyperglycemia pre- and post-ART. Results. Among 635 PLHIV, 97.3% were males with mean age of 30 years and median CD4 count of 207 cells/mm3. Pre-ART, prevalence of dyslipidemia was 65.4% and hyperglycemia was 10.4%. Risk factors for dyslipidemia include hyperglycemia (AOR 3.8, p 0.001) and >320 days delay in ART initiation from HIV confirmation (AOR 1.5, p 0.032), while dyslipidemia was associated with hyperglycemia (AOR 3.1, p 0.001). Post-ART, prevalence of dyslipidemia was 48.6% and hyperglycemia was 15.6%. Risk factors for post-ART dyslipidemia include being WHO stage 4 (AOR 2.1, p 0.021), hyperglycemia (AOR 16.1, p<0.001), >36 months ART duration (AOR 8.7, p<0.001) and efavirenz-based ART (AOR 2.8, p<0.001). Low CD4 count post-ART had a negative correlation with dyslipidemia (AOR 0.5, p 0.005). Post-ART hyperglycemia was associated with age >30 years (AOR 2.1, p 0.004), being overweight (AOR 1.8, p 0.023), dyslipidemia (AOR 17.8, p<0.001) and zidovudine-based ART (AOR 1.4, p 0.051). Conclusion. Dyslipidemia and hyperglycemia prevalence was high in Filipino PLHIV. Traditional, HIV and treatment related factors contributed to its development. Intensive monitoring and initiation of appropriate treatment is recommended.